On Dimensions of OTA Setups for Massive MIMO Base Stations Radiated Testing - Kyosti, Pekka; Wei Fan; Pedersen, Gert Frolund; Latva-Aho, Matti (IEEE access, 2016)
The development of base stations (BSs) with large aperture antenna arrays, enabled partially by the utilization of cmWave and mmWave frequency bands, will require radiated testing in fading conditions. In this paper, the objective is to investigate the suitable measurement distances and physical dimensions of the over-the-air setups for the performance evaluation of massive multiple-input multiple-output (MIMO) BSs in anechoic chambers with multiple probes. Setup dimension is the major cost factor in the test systems and is thus the key issue to be investigated. The purpose is to determine whether the conventional far field criteria must be followed when determining the range of the setup or if they can be relieved. The impact of limited test setup dimension on various metrics, e.g., far field criteria, field performance within the test area, system link budget analysis, direction of arrival estimation algorithm as well as multi-user MIMO sum-rate capacity are investigated to determine the range of the test setup. It was found that the link budget does not support for the measurement distances claimed by the Fraunhofer distance. Most of the utilized metrics, especially the sum rate capacity, indicate that smaller setup sizes can still yield reasonable measurement accuracy. Simulations were performed at 2.6, 3.5, and 28 GHz frequencies.